FSCN1 Promotes Esophageal Carcinoma Progression Through Downregulating PTK6 via its RNA-Binding Protein Effect - Cai, Hongfei; Wang, Rui; Tang, Ze; Lu, Tianyu; Cui, Youbin (Frontiers in Pharmacology, 2022)
Objective: Esophageal squamous cell carcinoma (ESCC) causes many deaths worldwide every year. Fascin actin-bundling protein 1(FSCN1) has been reported to be a promoter of ESCC via its actin-binding function, however, its new role as an RNA-binding protein (RBP) has not been investigated. Here, we explored the RBP role of FSCN1 in the development of ESCC. Methods: Whole-genome expression sequencing was performed to screen for altered genes after FSCN1 knockdown. RNA immunoprecipitation was performed to determine the target mRNA of FSCN1 as an RBP. In vitro experiments with ECA-109 and KYSE-150 and ex vivo experiments in tumor-bearing mice were performed to investigate the effects of FSCN1 and PTK6 on ESCC progression. Results: FSCN1 could downregulate mRNA and the protein level of PTK6. The binding position of PTK6 (PTK6-T2) pre-mRNA to FSCN1 was determined. PTK6-T2 blocked the binding between FSCN1 and the pre-mRNA of PTK6, and thus reversed the promotion effect of FSCN1 on ESCC tumor progression via the AKT/GSK3β signaling pathway. Conclusion: A novel effect of FSCN1, RBP-binding with the pre-mRNA of PTK6, was confirmed to play an important role in ESCC progression. PTK6-T2, which is a specific inhibitor of FSCN1 binding to the pre-mRNA of PTK6, could impede the development of ESCC.